Development of the Rapid Assessment, Prioritisation and Referral Tool (RAPaRT) for multidisciplinary teams in emergency care settings. Issue 1 (13th January 2014) - McPhail, Steven M; Vivanti, Angela; Robinson, Kate
Abstract : Objective: This investigation utilised the expertise of allied members of multidisciplinary teams working in emergency care settings to develop and validate a Rapid Assessment Prioritisation and Referral Tool (RAPaRT). This instrument is intended for use among patients (with non-life threatening acuity) presenting to emergency care settings to indicate when referral to an allied member of the multidisciplinary team is warranted. Method: This three stage instrument development and validation study included: a Delphi panel process to determine key criteria to guide instrument development and identify potential items to be carried forward for testing (stage 1); a prospective cohort of consecutive admissions (n=153) to investigate item sensitivity and specificity and retain only the most suitable items (stage 2); then final consultation with the Delphi panel to ensure the final instrument was clinically amenable (stage 3). Results: 23 potential items were identified following stage 1. At the completion of item sensitivity and specificity analysis and in consultation with the Delphi panel, seven items were retained in the instrument. Area under the receiver operating characteristic curve was 0.803 for these seven items in predicting when a referral was warranted. Final consultation with the Delphi panel members also resulted in the addition of an open ended (eighth) item to allow description of any infrequent, but important, reason for referral. Conclusions: The RAPaRT has demonstrated substantial promise as an efficient clinically amenable instrument to assist multidisciplinary teams in emergency care settings. Further research to investigate the wider implementation of the RAPaRT is warranted.